2012
DOI: 10.5539/jmsr.v1n2p207
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ZnO substituted 45S5 Bioactive Glasses and Glass - Ceramics

Abstract: ZnO substituted 45S5 bioactive -glasses and glass -ceramics were prepared. In vitro bioactivity of bioactive glasses and glass -ceramics, before and after exposed to simulated body fluid (SBF) solution for different time periods, were investigated by fourier transform infrared (FTIR) reflectance spectrometer with measuring the pH and the concentrations of silicon, sodium, calcium, phosphorus and zinc ions in SBF solution. The density, micro hardness and flexural strength of bioactive glasses and glass -ceramic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 5 publications
5
34
2
Order By: Relevance
“…FT-IR studies clearly indicate that all glass ceramic samples show bone bonding ability. The addition of ZnO has not decreased the formation of HCA layer, in contrary to the results by Srivastava and Pyare [7] where the addition of >1 % ZnO into the system decreased the formation of the apatite layer. In our study it was found that increasing the concentration of ZnO (particularly >3.63 mol %) in the system predominantly reduced the degree of crystallization of the system which was confirmed by XRD ( Fig.…”
Section: Structural Characterizationcontrasting
confidence: 53%
See 3 more Smart Citations
“…FT-IR studies clearly indicate that all glass ceramic samples show bone bonding ability. The addition of ZnO has not decreased the formation of HCA layer, in contrary to the results by Srivastava and Pyare [7] where the addition of >1 % ZnO into the system decreased the formation of the apatite layer. In our study it was found that increasing the concentration of ZnO (particularly >3.63 mol %) in the system predominantly reduced the degree of crystallization of the system which was confirmed by XRD ( Fig.…”
Section: Structural Characterizationcontrasting
confidence: 53%
“…The nucleation temperature at 740°C and crystallization temperature at 910°C for the parent glass (BZnO) was reduced to 654°C and 746°C, respectively, after 15.53 mol % substitution of ZnO into the system. This result can be attributed to the decrease in viscosity of the system with the increase of ZnO as reported by Doremus [14] and Alizadeh et al [15], Kamitakahara et al [11], Mirhadi et al [16] and Srivastar and Pyare [7].…”
Section: In Vitro Bioactivity Analysissupporting
confidence: 50%
See 2 more Smart Citations
“…Figure 1 shows the FTIR spectra for BG particles, PU scaffold and PU-BG scaffolds. The FTIR spectra for BG particles showed the existence of Si-O-Si bending vibrations at 499 cm -1 , Si-O stretching at 934 cm -1 and asymmetric Si-O-Si stretching band at 1029 cm -1 [4]. The FTIR spectra for 0BG scaffold shows the PU characteristic bands since no BG particles were introduced into the samples.…”
Section: Characterizationsmentioning
confidence: 94%